Pineapple Juice Therapy Reduces Pain in Gout Sufferers - Mustikawati, Mustikawati; Rafferiany, Putri Marsha; Karina, Aulia Hira (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Gout is caused by hyperuricemia, which is a condition of high levels of uric acid in the blood. If uric acid levels increase, rheumatic pain can occur in the joints, pain, tenderness, redness and swelling. Data from the DKI Jakarta health service in 2018 estimated that 47.83% of elderly people suffered from gout, while in the South Tangerang area it was 6.38%. The aim of this case study is to describe the application of pineapple juice therapy to reduce pain in gout sufferers. This case study research method uses a qualitative descriptive method. Data collection used was interviews, physical examination and observation. The research subjects were 5 people who were given therapy for 5 - 7 days. When applying pineapple juice therapy, the results were a significant reduction in the pain scale and uric acid levels. Before administering therapy, the pain scale results were 7-8 and the uric acid levels were 8.9 mg/dl - 10.2 mg/dL. After giving therapy, the results showed a decrease in the pain scale between pain scale 1 and pain scale 2 as well as uric acid levels with results of 6.2 mg/dl - 6.8 mg/dL. It can be concluded that giving pineapple juice therapy is effective in reducing pain and reducing uric acid if respondents maintain a diet such as not consuming foods high in purine, and drinking water as needed.